Analysis of microbial community evolution, autolysis phenomena, and energy metabolism pathways in Pholiota nameko endophytes - Zhao, Huan; He, Yan; Wang, Yichu; He, Xiaolong; Zhao, Ruihua; Liu, Bo (Frontiers in Microbiology, 2024)
Introduction Pholiota nameko is a widely consumed edible fungus. This study focuses on two crucial developmental stages of Pholiota nameko, namely, mycelium and ascospores. The objectives of this research were to investigate changes in microbial diversity and community structure during the growth of Pholiota nameko and to analyze the adaptability of the dominant strains to their respective habitats through metabolic. Methods Specifically, we conducted second-generation sequencing of the 16S rRNA gene (Illumina) on samples obtained from these stages. In addition, we isolated and characterized endophytes present in Pholiota nameko, focusing on examining the impact of dominant endophyte genera on autolysis. We also conducted a metabolic pathway analysis. Results and discussion The results unveiled 578,414 valid sequences of Pholiota nameko endophytic fungi. At the phylum level, the dominant taxa were Basidiomycota, Ascomycota, Zoopagomycota, and Mucoromycota. At the genus level, the dominant taxa observed were Pholiota, Inocybe, Fusarium, and Hortiboletus. For endophytic bacteria, we obtained 458,475 valid sequences. The dominant phyla were Proteobacteria, TM6, Firmicutes, and Bacteroidetes, while the dominant genera were Edaphobacter, Xanthomonas, Burkholderia, and Pseudomonas. Moreover, we identified the isolated strains in Pholiota nameko using 16S rDNA, and most of them were found to belong to the genus Pseudomonas, with Pseudomonas putida being the most prevalent strain. The findings revealed that the Pseudomonas putida strain has the ability to slow down the breakdown of soluble proteins and partially suppress the metabolic processes that generate superoxide anion radicals in Pholiota nameko, thereby reducing autolysis. Additionally, our results demonstrated that molybdenum enzyme-mediated anaerobic oxidative phosphorylation reactions were the primary energy metabolism pathway in the Pseudomonas putida strain. This suggests that the molybdenum cofactor synthesis pathway might be the main mechanism through which Pholiota nameko adapts to its complex and diverse habitats.